Content Analyses of Scientific Articles from Issues Published in Sport Mont Journal in 2012 - Jovan Radulovic (Journal of Anthropology of Sport and Physical Education)
Sport Mont Journal is an electronic and printed scientific journal aimed at facilitating access to scientific knowledge for the purpose of raising global awareness of sports. So far, more than 1000 scientific papers from around the world have been published. Sport Mont Journal is indexed in over 23 international databases. Scopus is one of the most prestigious bases, making clear the quality of this magazine. Sport Mont covers all aspects of sports science and medicine, all clinical aspects of exercise, health and sport, physiology and biophysical search of sports performances, biomechanics, sports nutrition, rehabilitation, physical therapy, sports psychology, sports pedagogy, sports history, sports philosophy, sociology of sports , sports management and all aspects of scientific support to sports trainers from the natural, social and humanistic side. The aim of the paper was to classify titles in their fields of science. The sample of this research consisted of 94 titles, Sport Mont Journal published in 2012. The method of content analysis concluded that the most read works from the anthropology of sports - 45, then research in sport and sociopsychology - 14, then sports methodology, education and sports, management and marketing in sport - 18, the field of biomechanics includes – 4, physiology of sport - 2, methodology – 3, and, ultimately, sports medicine - 7. It should be noted that the authors of these works were from the whole region, and even wider.